Factors that influenced the spread of islam in the Golden Horde (Journal of history, 2021)
Although Islam began to penetrate the territory of Kazakhstan at the beginning of the 8th century, the complete Islamization of the population was during the Golden Horde (half of the 14th century). Therefore, the period of the Golden Horde is very important in the formation of the traditional religious worldview of the Kazakh people. Until the first quarter of the 13th century, Islam was the religion of the majority of the population in Central Asia. However, after the Mongol invasion, Islam lost its leading position and became one of the many religions in the vast empire. In the first years of the Golden Horde, there was a great competition between religions to dominate the public consciousness. But Islam soon took the lead at the end of this struggle. The process of Islamization of the Golden Horde, which began during the reign of Berke Khan, ended with the official religion of the state under the Uzbek Khan. This fact is confirmed by both historical and archaeological evidence. It can be argued that the spread of Is- lam in the Golden Horde was influenced by several cultural, social, economic, and geopolitical factors. Islam, in turn, not only won the struggle for the spirituality of the people, but also played a significant role in the history of the Golden Horde.Key words: The Golden Horde, religion, Islamization, Turkic peoples, Mongols.